2022
DOI: 10.1002/jms.4803
|View full text |Cite
|
Sign up to set email alerts
|

Time‐of‐flight secondary ion mass spectrometry imaging in cultural heritage: A focus on old paintings

Abstract: Time-of-flight secondary ion mass spectrometry (TOF-SIMS) imaging is a surface analysis technique that identifies and spatially resolves the chemical composition of a sample with a lateral resolution of less than 1 μm. Depth analyses can also be performed over thicknesses of several microns. In the case of a painting cross section, for example, TOF-SIMS can identify the organic composition, by detecting molecular ions and fragments of binders, as well as the mineral composition of most of the pigments. Importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 118 publications
0
5
0
Order By: Relevance
“…While small manuscript fragments exist (Dead Sea scrolls pieces for instance), solutions must be found to adapt the technique to avoid cutting large pieces in precious manuscripts. For example, it has been shown that microscopic removal of material from the surface is acceptable and sufficient for medieval painting studies with ToF-SIMS [ 34 , 35 ]. Similarly, with due authorizations, it could be allowed to remove tiny parchment pieces from hidden regions e.g.…”
Section: Resultsmentioning
confidence: 99%
“…While small manuscript fragments exist (Dead Sea scrolls pieces for instance), solutions must be found to adapt the technique to avoid cutting large pieces in precious manuscripts. For example, it has been shown that microscopic removal of material from the surface is acceptable and sufficient for medieval painting studies with ToF-SIMS [ 34 , 35 ]. Similarly, with due authorizations, it could be allowed to remove tiny parchment pieces from hidden regions e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A further development of SIMS technology are nano-SIMS applications, which are characterised by a particularly high spatial resolution. SIMS platforms have been widely used for the study of ancient paintings [ 74 ]. In addition, other materials such as glass or bronze were also analysed [ 75 ].…”
Section: Sampling Strategiesmentioning
confidence: 99%
“…The third review, by Bouvier et al contained 134 references and focussed on the TOF-SIMS analysis of old paintings. 379 The method is capable of determining the organic composition by detecting the molecular ions and fragments of binders as well as the mineral contents of most of the pigments. The technique is almost non-destructive and has…”
Section: Organic Originmentioning
confidence: 99%